Fiscal Transparency, Accountability, and Risk. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper surveys that state of fiscal transparency in the wake of the current crisis and looks at what can be done to improve it. It examines the relationship between fiscal transparency and fiscal outcomes; reviews progress in promoting greater fiscal transparency over the past decade; considers the lessons of the recent crisis for existing fiscal transparency standards, practices, and monitoring arrangements; and makes a series of recommendations for renewing the global fiscal transparency effort in the wake of the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet